Every Story Is Different: Experiences With Body Changes Related to Cancer - Cole, Linda; Easley, Julie; Grightmire, Leslie; Lakshmanan, Ellil Mathiyan; Matthias, Sharon J.; McBoyle, Karen; Piercell, Emily; Purdy, Amelia; Schneider, Nancy; Wassersug, Richard J.; Martino, Rosemary; Fitch, Margaret I. (Frontiers in Psychology, 2022)
One of the important aspects of stakeholder engagement in cancer care and system planning is hearing from individuals who have been diagnosed with cancer about the impact of the diagnosis and treatment on their lives. Hearing stories from the perspectives of cancer survivors offers opportunity to gain new insight and understanding about experiences of being diagnosed and treated for cancer. This article presents ten short narratives about survivors' perspectives on body image and cancer. Each story is unique but, taken together, the picture they create is one of facing challenges, discovering personal resilience, and moving forward to engage in living. The stories emphasize the importance of communication and support from healthcare providers and understanding needs for a person-centered cancer care system.